(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: As the antifungal resistance has taken a massive proportion in the present date, Antifungal resistance is increasing due to irrational prescribing, over-the-counter use, and lack of awareness, leading to reduced drug effectiveness. There is a need for antifungal stewardship; however, limited information is available on the knowledge, attitudes, and practices of health sciences students regarding antimicrobial resistance. Methods: A cross-sectional survey was distributed to 1000 health sciences students, of which 752 completed the questionnaire and were included in the analysis. Results: Out of all respondents, 80.3% had good knowledge, 82.4% showed favorable attitudes, and 67.95% demonstrated good practices. Knowledge and attitudes improved significantly with the year of study (p < 0.001), and practices also showed a significant association (p = 0.032). Female students had higher knowledge but lower practice levels. Urban residence was linked to better preventive practices but lower knowledge and attitudes. Conclusion: Students showed good levels of knowledge and favorable attitudes toward antifungal resistance and stewardship, yet their practices were not always appropriate. Variations across gender, residence, and academic year underline the importance of early stewardship education, improved awareness, and stronger regulation of antifungal use to reduce resistance risks.